Analisis Strategi Pemasaran Usaha Rumah Tangga Pembibitan Buah Pada CV. Jaya Mandiri Argo Di Kecamatan Pekalongan Lampung Timur - Anisa Restu Pinuji; Ana Septiani; Kuncoro Budi Riyanto (Jurnal Manajemen DIVERSIFIKASI, 2025)
Competition in the fruit breeding business in Pekalongan sub-district is getting tighter, both on a small and large scale. So it requires every manager to maintain and improve the marketing strategy they carry out so that managers are able to develop their business and can adapt to the company's external environment which requires ever-changing developments. With the various kinds of fruit breeding businesses that exist, this causes consumers to move from one place to another. Seeing this phenomenon, managers should be able to fulfill what consumers need and expect. A company's promotional activities are carried out as well as possible, namely by planning, directing, controlling and budgeting in accordance with the company's financial conditions. This research aims to find out the strategy of internal factors, external factors and business marketing strategies in CV. Jaya Mandiri Argo fruit breeding households. This research is qualitative research using a descriptive approach. Data collection uses observation, interviews, documentation and literature study. Data analysis uses SWOT analysis (Strength, Weakness, Opportunity, Threat) to find out the strengths, weaknesses, opportunities and threats of the business marketing strategy carried out by CV. Jaya Mandiri Argo. Research results using SWOT analysis showed 7 strengths, 3 weaknesses, 3 opportunities and 2 threats. Then do the weighting, rating and score with IFAS. EFAS is in the growth quadrant (very profitable). So the application of using the SWOT matrix is ​​by using the SO strategy, which uses strengths to take advantage of existing opportunities by overcoming the weaknesses it has, and the alternative strategy is using the WT strategy